Spelling Ability in College Students Predicted by Decoding, Print Exposure, and Vocabulary. Issue 1 (2nd January 2017) - Ocal, Turkan; Ehri, Linnea
Abstract : This study examines students' exposure to print, vocabulary and decoding as predictors of spelling skills. Participants were 42 college students (Mean age 22.5, SD = 7.87; 31 females and 11 males). Hierarchical regression analyses showed that most of the variance in spelling was explained by vocabulary knowledge. When vocabulary was entered first into the regression model, exposure to print and decoding were no longer significant predictors. However, both decoding and print exposure were significant predictors of vocabulary. The three predictors together explained about 43 % of variance in spelling skills. Results suggest that an important source of individual differences in spelling knowledge arises from the acquisition of vocabulary words when decoding skill is applied to read words encountered during the wide reading of text.